Primary pulmonary angiosarcoma: Three case reports and literature review. Issue 5 (28th July 2016) - Ren, Yanhong; Zhu, Min; Liu, Yan; Diao, Xiaoli; Zhang, Yuhui
Abstract : Primary pulmonary angiosarcoma is a rare type of malignant vascular tumor with a very aggressive clinical course and a grim prognosis. To date, only a handful of cases have been reported in English literature. Its rarity and consequent low index of suspicion makes clinical diagnosis difficult. In this report we present three cases of primary pulmonary angiosarcoma with cough, hemoptysis, and progressive dyspnea to contribute to the sparse literature on this disease. A review is made of previous reports of primary pulmonary angiosarcomas, and the clinical characteristics, diagnosed method, treatment options, and prognosis of pulmonary angiosarcoma are also discussed.